Conflict management - Henry, Michael; Collins, Cath; Video Education Australasia (Victoria : Video Education Australasia, 2007)
This program provides a dramatic perspective on the place of conflict in workplace communications and explores strategies for dealing with everyday conflict situations
Title from container
Executive producer : Mark McAuliffe ; senior producer : Richard Leigh ; sound : Alexy Gudimenko ; editor : Michael Henry ; camera : Zane Lovitt
Voice over : Mike McEvoy
Keywords: Conflict management; Conflict (Psychology); Stress (Psychology); Interpersonal relations